2015
DOI: 10.3389/fnsys.2014.00245
|View full text |Cite
|
Sign up to set email alerts
|

Activation and inhibition of posterior parietal cortex have bi-directional effects on spatial errors following interruptions

Abstract: Interruptions to ongoing mental activities are omnipresent in our modern digital world, but the brain networks involved in interrupted performance are not known, nor have the activation of those networks been modulated. Errors following interruptions reflect failures in spatial memory, whose maintenance is supported by a brain network including the right posterior parietal cortex (PPC). The present study therefore used bi-directional transcranial Direct Current Stimulation (tDCS) of right PPC to examine the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…Right AIPS stimulation improved performance in the more difficult tracking load condition where participants’ accuracy was relatively low (~70%) whereas stimulation did not affect performance in the easier tracking load condition (85–90%) where participants were performing at or close to ceiling. These results are consistent with the a priori hypotheses and are in line with the previous literature that suggests that tDCS is more beneficial to novices (Bullard et al, 2011 ) and lower performers (Tseng et al, 2012 ; Blumberg et al, 2014 ; Foroughi et al, 2015 ) and may be more effective when paired with difficult tasks (Jones and Berryhill, 2012 ; Berryhill et al, 2014 ). Additionally, cognitive training is not beneficial for individuals already performing at ceiling (Ball et al, 2007 ; Schmiedek et al, 2010 ; Jaeggi et al, 2011 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Right AIPS stimulation improved performance in the more difficult tracking load condition where participants’ accuracy was relatively low (~70%) whereas stimulation did not affect performance in the easier tracking load condition (85–90%) where participants were performing at or close to ceiling. These results are consistent with the a priori hypotheses and are in line with the previous literature that suggests that tDCS is more beneficial to novices (Bullard et al, 2011 ) and lower performers (Tseng et al, 2012 ; Blumberg et al, 2014 ; Foroughi et al, 2015 ) and may be more effective when paired with difficult tasks (Jones and Berryhill, 2012 ; Berryhill et al, 2014 ). Additionally, cognitive training is not beneficial for individuals already performing at ceiling (Ball et al, 2007 ; Schmiedek et al, 2010 ; Jaeggi et al, 2011 ).…”
Section: Discussionsupporting
confidence: 91%
“…We anticipated that an effect of tDCS would be greatest for the high tracking load and may even be absent in the low load condition due to ceiling effects for tasks already at or near ceiling in performance (Ball et al, 2007 ; Schmiedek et al, 2010 ; Jaeggi et al, 2011 ). In addition, previous researchers have suggested that tDCS may be more beneficial for novices/lower performers than for experts/higher performers (Bullard et al, 2011 ; Tseng et al, 2012 ; Blumberg et al, 2014 ; Foroughi et al, 2015 ) and that tDCS may be more effective in difficult tasks (Berryhill et al, 2014 ), suggesting that both task difficulty and individual abilities may play a critical role in the effectiveness of stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…The first system postulated by their model, contention scheduling (CS), would select the highest activation, generating the action and managing interference. Thus an interruption might result in selecting inappropriate action schemata, causing errors after resumption (Foroughi et al, 2015;Reason, 1990). By contrast, willed or novel actions need greater attentional control because the action schemata are either inappropriate or absent.…”
Section: Attention and Working Memory Models Accounting For The Effecmentioning
confidence: 99%
“…This is why the resumption lag (RL) has been proposed (Trafton, Altmann, Brock, & Mintz, 2003) and corresponds to the time necessary to resume the main task after an interruption. Accuracy has been reported in many experiments but seems less sensitive to interruptions (Bailey & Konstan, 2006;Botvinick & Bylsma, 2005;Foroughi, Blumberg, & Parasuraman, 2015). However, Reason (1990) suspected that omissions might increase after inter-ruptions.…”
mentioning
confidence: 99%
“…Finally, transcranial direct current stimulation (tDCS) has been shown to reduce the number of spatial errors individuals make following interruptions by 25%, but a majority (i.e., 75%) of the errors still occurred (Foroughi, Blumberg, et al, 2015). The majority of previous research has focused on the aforementioned mitigation methods, with few efforts to examine alternative methods that may be able to mitigate the disruptiveness of interruptions.…”
mentioning
confidence: 99%